ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEMITRAAN BISNIS PT PLN (Studi Kasus Pada Kemitraan PT. PLN dengan AKLI Wilayah Kota Malang) - Amerieska, Siti; -, Nurhidayah (JURNAL MANAJEMEN DAN AKUNTANSI, 2014)
Partnership one of the way alternative strategic for increase performance evaluation in organization business.Partnershipâ it could be happen both oftim when they have good synergy.PT PLN and AKLI have partnership in relationship in Â procurement of goods and service. The aims of this research to anaylize how partnership between PT PLN and AKLI Â cases.Using eksplanatory research distribute quesionare 54 vendor, with SPSS tool, actually the result that have 5 factor influence performance partnership. The are communication effective, sutanability, financial guaranted, mutual trust,time period and environment flexibility.Financial granted has the big influence for performance partnership. Key words: partnership, financial guaranted, communication effective.